The 5HT4R agonist velusetrag efficacy on neuropathic chronic intestinal pseudo-obstruction in PrP-SCA7-92Q transgenic mice - Liu, Yongqiang; Wu, Yunfei; Ren, Dewan; Tao, Yulong; Mai, Fangyi; Zhu, Jingyi; Li, Xiang; Colla, Emanuela; Grimaldi, Maria; Giovannini, Roberto; Giorgi, Fabrizio; Vesci, Loredana (Frontiers in Pharmacology, 2024)
Background: Chronic intestinal pseudo-obstruction (CIPO) is a type of intestinal dysfunction with symptoms of intestinal blockage but without the actual mechanical obstruction. Currently there are no drugs available to treat this disease. Herein we report the characterization of the PrP-SCA7-92Q transgenic (Tg) line as a valuable CIPO mouse model and investigated the tolerability and efficacy of the 5-hydroxytryptamine type-4 receptor (5HT4R) agonist velusetrag as a promising pharmacological treatment for CIPO. Methods: To test the pharmacodynamics of velusetrag, 8-week-old SCA7 Tg mice, which express human mutated Ataxin-7 gene containing 92 CAG repeats under the mouse prion protein promoter were treated for 5 weeks by oral route with velusetrag at 1 and 3 mg/kg or vehicle. Body weight was monitored throughout the treatment. After sacrifice, the small intestine and proximal colon were collected for whole mount immunostaining. Untreated, age matched, C57BL/6J mice were also used as controls in comparison with the other experimental groups. Results: Analysis of SCA7 Tg mice showed tissue damage and alterations, mucosal abnormalities and ulcers in distal small intestine and proximal colon. Morphological changes were associated with significant neuronal loss as shown by decreased staining of pan-neuronal markers, and with accumulation of ataxin-7 positive inclusions in cholinergic neurons. Administration of velusetrag reversed intestinal abnormalities, by normalizing tissue damage and by re-establishing normal level of glia/neuron’s count in both the small and large intestine. Conclusion: We demonstrated that the PrP-SCA7-92Q Tg line, a model originally developed to mimic spinocerebellar ataxia, is suitable to study CIPO pathology and can be useful to establish new therapeutic strategies, such as in the case of velusetrag. Our results suggest that velusetrag is a promising compound to treat patients affected by CIPO or intestinal dysmotility disease.